Bridging the Gap Between the World of Education and the World of Business via Standards to Develop Competences of the Future at Universities - Paweł Poszytek (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The author of this article has proven in a separate bibliometric analysis that in most cases the world of education and the world of business use different terminology when discussing the competences needed on the current and future labor market. The former tends to refer to competences of the future while the latter uses the term competences 4.0 more often, which results from binding this phenomenon with the digital transformation and current changes in industry generally called the 4th industrial revolution. The differences in terminology in this respect also refer to the way these competences are defined, although in most cases they refer to three main domains: (1) technical competences; (2) cognitive competences and (3) social competences. On the basis of the above, the research group of the Polish NGO, The Platform for the Industry of the Future, designed the certification system for universities which would like to be labelled as universities that educate for the future and develop the competences of the future among their students. This certification system is based on the following standard: (1) curriculum; (2) internal ecosystem at a university; (3) cooperation with an external ecosystem; (4) the teaching staff and (5) infrastructure at a university. The certification system provides and defines detailed criteria for each element of the standard mentioned above, as well as indicators that measure the fulfilment of these criteria.